Macimorelin (AEZS-130)-Stimulated Growth Hormone (GH) Test: Validation of a Novel Oral Stimulation Test for the Diagnosis of Adult GH Deficiency - Garcia, J. M.; Swerdloff, R.; Wang, C.; Kyle, M.; Kipnes, M.; Biller, B. M. K.; Cook, D.; Yuen, K. C. J.; Bonert, V.; Dobs, A.; Molitch, M. E.; Merriam, G. R. (The journal of clinical endocrinology and metabolism, 2013)
Context:In the absence of panhypopituitarism and low serum IGF-I levels, the diagnosis of adult GH deficiency (AGHD) requires confirmation with a GH stimulation test. Macimorelin is a novel, orally active ghrelin mimetic that stimulates GH secretion.Objective:The objective of the study was to determine the diagnostic efficacy and safety of macimorelin in AGHD.Design:This was a multicenter open-label study comparing the diagnostic accuracy of oral macimorelin with that of arginine+GHRH in AGHD patients and healthy, matched controls. After 43 AGHD patients and 10 controls were tested, the GHRH analog Geref Diagnostic [GHRH(1–29)NH2] became unavailable in the United States. The study was completed by testing 10 additional AGHD patients and 38 controls with macimorelin alone.Main Outcome Measure:Peak GH area under the receiver operating characteristic curve after macimorelin was measured.Results:Fifty AGHD subjects and 48 controls were evaluated. Peak GH levels in AGHD patients and controls after macimorelin were 2.36 ± 5.69 and 17.71 ± 19.11 ng/mL, respectively (P < .0001). With macimorelin, the receiver operating characteristic analysis yielded an optimal GH cut point of 2.7 ng/mL, with 82% sensitivity, 92% specificity, and 13% misclassification rate. For subjects receiving both tests, macimorelin showed discrimination comparable with arginine+GHRH (area under the receiver operating characteristic curve 0.99 vs 0.94, respectively, P = .29). Obesity (body mass index > 30 kg/m2) was present in 58% of subjects, and peak GH levels were inversely associated with body mass index in controls (r = −0.37, P = .01). Using the separate cut points of 6.8 ng/mL for nonobese and 2.7 for obese subjects reduced the misclassification rate to 11%. Only 1 drug-related serious adverse event, an asymptomatic QT interval prolongation on the electrocardiogram, was reported.Conclusion:Oral macimorelin is safe, convenient, and effective in diagnosing AGHD with accuracy comparable with the arginine+GHRH test.